A Semiotic Analysis Of Grabbike Advertisement Using Roland Barthes' Theory - Salfiyaningsih; Yusuf Zaenal Muttaqin; Hilmi Ali Salama; Salamah Rizki Utami; Siti Komariah; Mayang Pipit (International journal of technology and education research, 2026)
Advertising functions not only as a promotional medium but also as a cultural text that conveys ideological meanings through visual and verbal signs. This study aims to analyze the meanings embedded in a GrabBike advertisement featuring the Indonesian comedian and actor Mas Adam (Inul Daratista’s husband) by employing Roland Barthes' semiotic framework. The study applies a qualitative descriptive method focusing on Barthes' two orders of signification: denotation and connotation, as well as myth. The findings reveal that the advertisement constructs meanings beyond its literal promotional message. At the denotative level, the advertisement presents a GrabBike rider identified as Mas Adam, accompanied by promotional text highlighting affordable daily transportation costs. At the connotative level, the visual and verbal elements signify affordability, reliability, and familiarity, while the use of a well-known public figure reinforces trust and cultural proximity with Indonesian consumers. At the mythological level, the advertisement naturalizes the ideology that digital transportation services are economical, accessible, and constitute an integral part of everyday urban life. The study demonstrates that advertising not only sells services but also shapes social perceptions and consumer lifestyles.